Multiple criteria decision support system for the assessment of energy generation technologies considering the dimension of values - Šliogerienė, Jūratė; Kaklauskas, Artūras; Štreimikienė, Dalia; Bianchi, Massimo (International Journal of Strategic Property Management, 2012)
Comprehension of the effect of energy generation technologies on the natural environment, human health and safety leads to a new and responsible approach to the choice and development of technologies. When it comes to preparing energy growth scenarios and handling issues related to the choice and assessment of technologies, environmental studies must be in a particular spotlight. One way to make quantitative and qualitative assessment of the effect of technologies on the environment is through a thorough integrated analysis, which, in addition to economic and technical solutions, also considers other aspects of concern to the public. A changed environment demands for systems of criteria which help consider its changes, the attitudes of the general public, public sentiments toward the effect of technologies, public values and community involvement in the process of important decision-making. The article examines how the dimension of values affects the analysis of the impact of environmental factors on the value of energy generation technologies. It presents a set of criteria for the assessment of energy generation technologies; the set, in addition to technological, economic and environmental criteria, includes criteria which reflect the values. The article also introduces the expert decision support system EGTAV-SPS, which helped assess the effect of environment on energy production technologies.First Publish Online: 19 Dec 2012